Application of Rational Emotive Therapy (TRE) in overcoming the anxiety of children who are victims of bullying at SMP Negeri 1 Sambit Ponorogo, East Java, Indonesia - Syahrudin; Zakiah Binti Mohamad Ashari; Beti Malia Rahma Hidayati (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
The process of implementing counseling guidance used by guidance and counseling teachers in Class IX B at SMP Negeri 1 Sambit Ponorogo is very important, with the existence of this counseling guidance at SMP Negeri 1 Sambit Ponorogo, students are prevented from unwanted problems or issues, in its implementation the theory of counseling guidance used by the guidance and counseling teacher in Class IX B at SMP Negeri 1 Sambit Ponorogo using Rational Emotive Therapy (TRE) which focuses on controlling irrational or irrational ways of thinking with the aim of thinking more rationally. This research aims to: 1) To find out the process of implementing counseling guidance using Rational Emotive Therapy (TRE). 2) To find out what approaches are used by guidance and counseling teachers in Class IX B at SMP Negeri 1 Sambit Ponorogo when providing counseling guidance with rational emotive therapy (TRE). 3) To find out the results of the counseling process using rational and emotional therapy itself. The results of research and data analysis that have been carried out regarding the implementation of counseling guidance with rational emotive therapy (TRE) provided by teachers in dealing with students' anxiety due to bullying in BK in Class IX B at SMP Negeri 1 Sambit Ponorogo can be seen that in providing the guidance process Students who are victims of bullying proceed in accordance with the rational emotive theory (TRE) with the approach used by the guidance and counseling teacher in Class IX B at SMP Negeri 1 Sambit Ponorogo in providing a counseling guidance process with rational emotive therapy to students which is good, namely by providing Varying approaches when solving problems provide different approaches, such as an individual approach that is oriented towards a sense of calm and comfort in dealing with problems.